Arterial blood pressure and heart rate regulation in shock state. Issue 5 (October 2015) - DellaVolpe, Jeffrey D.; Moore, Jason E.; Pinsky, Michael R.
<x xml:space="preserve">Abstract</x> Purpose of review Circulatory shock is a complicated problem that carries a high risk of complications and mortality for critically ill patients. The heart rate and blood pressure targets to which a patient in shock should be resuscitated remain a challenge to intensivists. Recent findings While the ideal blood pressure and heart rate in circulatory shock are still not definitive, recent studies have begun to refine these targets. A recent trial comparing a mean arterial pressure target of 80–85 mmHg with a target of 65–70 mmHg showed no difference in mortality, with a decreased need for renal replacement therapy in patients with pre-existing hypertension based on subgroup analysis. Regulation of heart rate was defined by a trial demonstrating that heart rate control in patients with severe sepsis on high-dose norepinephrine with esmolol titration did not result in additional adverse events. Summary The ideal target blood pressure in the resuscitation of circulatory shock is variable and likely depends on prior blood pressure. Heart rate regulation with β-blockade appears to be safe in selected patients when accompanied by adequate resuscitation and monitoring.